Impact of a Mindfulness-Based Weight-Loss Intervention on Sleep Quality Among Adults with Obesity: Data from the SHINE Randomized Controlled Trial - Adler, Elizabeth (J Altern Complement Med, 2017)
Background and Objective: Sleep disturbance is a common problem among adults with obesity. Mindfulness interventions have been shown to improve sleep quality in various populations but have not been investigated in adults with obesity. The aim of this study was to compare the effects of a mindfulness-based weight-loss intervention with an active control on self-reported sleep quality among adults with obesity. Method: This study was a secondary analysis of a randomized controlled trial and included 194 adults with a body mass index in the range 30–45 kg/m(2). The treatment intervention included mindfulness-based eating and stress-management practices, and the active control intervention included training in progressive muscle relaxation (PMR). Both groups received identical diet and exercise guidelines in 17 group sessions conducted over 5.5 months that were matched for time, attention, and social support. The primary outcome of this analysis was between-group change in self-reported sleep quality, which was assessed using the Pittsburgh Sleep Quality Index (PSQI) global score at baseline and at 6, 12, and 18 months. Results: Between-group differences in mean PSQI change scores in the mindfulness group (n = 100) compared to the control group (n = 94) were −0.27 (−0.68, 1.22; p = 0.58) at 6 months, −0.57 (−0.35, 1.50; p = 0.22) at 12 months, and −0.50 (−0.53, 1.53; p = 0.34) at 18 months, all in the direction of more sleep improvement in the mindfulness group but none reaching statistical significance. In the mindfulness group, average weekly minutes of meditation practice time was associated with improved sleep quality from baseline to 6 months. Conclusions: No statistically significant evidence was found that a weight-loss program that incorporates mindfulness improves self-reported sleep quality compared to a control diet/exercise intervention that included PMR. Within the mindfulness group, average weekly minutes of mindfulness practice was associated with improved sleep quality.